2005
DOI: 10.13031/2013.19178
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Load Estimation in Silage Harvesting

Abstract: There are many sources of disturbances for on-the-go weighing. This study was conducted to develop a new method to remove those disturbances and to estimate more accurate dynamic masses in silage harvesting. A mathematically simple procedure was developed using vertical movement information from a low-cost accelerometer, in addition to conventional instrumentation using load cells for mass data, and was tested using a small scale model weighing bin and a commercial silage wagon. Clear similarities were found b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…23,24 Tumors were identified in 3 patients (10%). This observation is in line with findings from the cohorts of Lai et al 2 (6 of 51 patients [12%] with 5 different tumors) and Shin et al 5 (1 of 14 patients [7%]) but contrasts with several studies 1,3,4 that found no tumor associations.…”
Section: Clinical and Cognitive Outcomessupporting
confidence: 90%
See 4 more Smart Citations
“…23,24 Tumors were identified in 3 patients (10%). This observation is in line with findings from the cohorts of Lai et al 2 (6 of 51 patients [12%] with 5 different tumors) and Shin et al 5 (1 of 14 patients [7%]) but contrasts with several studies 1,3,4 that found no tumor associations.…”
Section: Clinical and Cognitive Outcomessupporting
confidence: 90%
“…Patients with anti-LGI1 encephalitis presented with typical clinical symptoms (ie, FBDS and limbic encephalitis) complemented by hyponatremia and characteristic hippocampal MRI signal changes. 1,2,5,25,26 Twenty percent of the patients in our cohort had autonomic (eg, shivers, flushing) or pilomotor seizures. 23,24 Tumors were identified in 3 patients (10%).…”
Section: Clinical and Cognitive Outcomesmentioning
confidence: 98%
See 3 more Smart Citations